Analysis of the Influence of Taste, Quality of Ingredients, and Price on Customer Satisfaction of Meatballs of Rezeki Nganjuk - Teddy, Teddy; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2025)
Research Objectives: This study aims to analyze the influence of taste, ingredient quality, and price on customer satisfaction at Bakso Rezeki Nganjuk.Design/Method/Approach: This study uses a quantitative approach with survey techniques and questionnaire dissemination involving restaurant customers as respondents using the Lemeslow formula, with 97 respondents and using a statistical testResearch Findings: Based on these findings, it can be analyzed use statistical procedures so determine the predictive generalizations that have been made, that taste, and price have a significant influence on customer satisfaction, with taste being the most dominant factor. Meanwhile, the quality of the materials is not significant to customer satisfaction due to the absence of definite knowledge for the customer.Theoretical/Originality contribution: This research provides important insights for MSME managers to focus on improving Taste, Product Quality, and Appropriate Price to maintain Customer SatisfactionPractical/Policy Implications: results this study show that taste, quality of ingredients and price have a significant influence on customer satisfaction so there are implications that can be applied by the management of Bakso Rejeki, namely increasing customer satisfaction, improving taste, increasing taste consistency, choosing quality raw materials and managing the right price.Research limitations: Too little time and insufficient manpower so that this study is not optimal. This research is far from perfect, so further research is expected to be done better than before.